Variasi Spasial Pertumbuhan dan Produktivitas Padi Merah Akibat Pengairan Berbeda di Sawah Organik Desa Sengguruh, Kecamatan Kepanjen Kabupaten Malang - Tiara Ayu Pratiwi; Endang Arisoesilaningsih (Biotropika: Journal of Tropical Biology, 2014)
This study aimed to observe spatial variation of the Aek Sibundong red rice growth and productivity in three different areas of an organic rice field under different water logging levels, as well as to determine the interaction among rice growth with weeds and rice field’s abiotic factors on two planting seasons in the Sengguruh Village, Kepanjen District Malang Regency. Observations were conducted with a purposive sampling based on water logging in three areas. Red rice growths were observed in four growth phases: 20, 48, 82, 102 dap (days after planting) includes plant height, biomass, number of tillers and panicles, grain number and biomass. Weeds (taxa richness, % coverage and biomass) were observed using sampling plots of 0.25 m2. Abiotic factors include soil (pH, soil organic matter and soil bulk density) and rice field water (presence or absence of logging, pH, and conductivity). Data were analyzed using SPSS and PAST software. The result showed there were spatial variations of rice growth in three areas. Rice planted close by irrigation channel has taller plant height and more number of tillers and panicles but not significantly different from those planted in another two areas. However, rice planted close by irrigation channel tends to produces vegetative biomass and grain ten times more than those planted far by irrigation channel. Water logging decreased coverage and taxa richness of weeds. Some weeds after manual weeding had no effect on productivity of panicles and grains. High content of soils organic matter occurred at early vegetative phase and decreased at late reproductive phase, so the lower soils bulk density. Keywords: Growth, productivity, red rice, spatial variation